Diagnostic Approach and Management of Clostridium difficile Infection - Fransiscus Nikodemus Hosea; Achmad Fauzi (The Indonesian Journal of Gastroenterology, Hepatology and Digestive Endoscopy)
Clostridium difficile infection (CDI) was first viewed as a nosocomial infection as it is associated with antibiotics administration. But since antibiotics are more frequently to be prescribed in the community setting, clinicians should investigate the probability of all antibiotics-associated diarrhea as CDI.